Black Soybean-Based Tempeh Product Innovation to Enhance the Added Value of Local Food Products - Anisa Ayu Vernanda; Febrianti Alvia; Ameylia Monika; Tan Evan Tandiyono (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to develop an innovative tempeh product made from black soybeans to enhance the added value of local food products and promote the utilization of indigenous agricultural resources. Black soybeans were selected as the primary raw material because of their high protein content, antioxidant activity, and anthocyanin compounds, which provide greater functional benefits than conventional soybeans. This study employed an empirical qualitative approach using a descriptive research design. Primary data were collected through semi-structured interviews, direct observation of the production process, and documentation, while secondary data were obtained from relevant scientific literature. The production process included black soybean selection, washing, soaking, boiling, partial seed coat removal, inoculation with Rhizopus starter culture, packaging in banana leaves, and fermentation for one to three days. The findings indicate that black soybean tempeh was successfully produced with a compact texture, uniform white mycelial growth, a distinctive dark appearance, and sensory characteristics comparable to conventional tempeh. The innovation also demonstrates promising commercialization potential through product differentiation, functional food positioning, and market-oriented value creation. These findings suggest that black soybean-based tempeh can increase the economic value of local food products, encourage food diversification, and provide sustainable business opportunities for micro, small, and medium-sized enterprises (MSMEs).